Factors Motivating Public School Teachers to Enroll their Children in Private Schools: A Phenomenological Study - Niure, Dhruba Prasad (Education and Development, 2021)
This study aims at exploring the motivating factors that encourage public school permanent teachers to enroll their children in private schools. To achieve this objective, the study was guided by interpretive paradigm followed by phenomenological research design. Altogether eight teachers were chosen from eight government-funded schools located in Bagmati province, following purposive sampling method. And then qualitative information was garnered by using in-depth interview to get a deeper understanding on the motivating factors that captivate public school teachers to send their children to private schools. Furthermore, collated data were edited, transcribed, coded, and thematized to draw meaningful results and conclusions for attaining the objective of the study. A number of factors such as quality education, English medium, regular homework, accessibility of private schools, disciplined environment, sound administration, political neutrality, and the like were found playing crucial role for motivating public school teachers towards private schools; and many of them send their children to private schools with the intention of receiving quality education services. This trend creates difficulties in ensuring the constitutional rights of children to receive quality education free of cost upto secondary level. Responsible agencies, therefore, need to pay proper attention to optimize the quality of public schools to ensure the rights to education for all children as enshrined in the constitution.